Oral hygiene in patients using removable dentures - Szalewski, Leszek; Pietryka-Michałowska, Elżbieta; Szymańska, Jolanta (Polish Journal of Public Health, 2017)
Introduction. Properly designed and used denture is conducive to proper rehabilitation of edentulism.Aim. The aim of the study was to assess the knowledge and hygiene habits of patients using removable partial dentures (RPDs) including selected sociodemographic characteristics.Material and methods. The survey comprised 321 individuals wearing RPDs, the residents of the Lublin Province. They were asked about the age, gender, place of residence, education, duration of denture usage, repairs made to RPDs, preparations used for cleansing and disinfection of RPDs, storage at night, causes of visiting the dentist, which was associated with the use of the RPD and the frequency of visits. The results were statistically analyzed.Results. The average duration of removable partial dentures use was 7.8±5.7 years. The vast majority of respondents cleaned RPDs with a toothpaste – 90.9%, almost 2/3 of the surveyed population – did not disinfect their RPDs, 56.4% people not remove them for the night. Only 3.7% people visited the dentist on regular basis associated with the use of RPDs.Conclusions. Among people wearing RPDs, too long duration of current RPD usage is confirmed. Moreover, the dentist does not check them regularly because patients do not visit dentists for check-up. RPDs are cleaned using improper preparations and usually are not disinfected. They are inadequately kept at nighttime, if ever removed from the mouth during sleep. Incorrect handling related to the use of removable partial dentures applies to persons regardless of their level of education and place of residence.